Activated sludge and other aerobic suspended culture processes. (16th September 2020) - Ouyang, Jia; Li, Chunying; Wei, Li; Wei, Dong; Zhao, Min; Zhao, Zhen; Zhang, Jie; Chang, Chein‐Chi
Abstract: This paper provides an overview of activated sludge related to suspended growth processes for the year 2019. The review encompasses process modeling of activated sludge, microbiology of activated sludge, process kinetics and mechanism, nitrogen and phosphorus control, design, and operation in the activated sludge field. The fate and effect of xenobiotics in activated sludge, including trace organic contaminant and heavy metal xenobiotics, which had influence on the growth of suspended sludge, are covered in this review. Compared to past reviews, many topics show increase in activity in 2019. These include, biokinetics process of aerobic granular sludge formation, pyrolysis kinetic mechanism of granular sludge. These topics are referred to formation and disintegration of granular sludge. Other sections include activated sludge settling model, toxicity resistant microbial community, nitritation–anammox processes for nitrogen removal, and respirometry used in the operation of real wastewater treatment plant are especially highlighted in this review. Practitioner Points: Biokinetics process of aerobic granular sludge formation Toxicity resistant microbial community in activated sludge Nitritation‐anammox processes for nitrogen removal in activated sludge